Composite photo-thermal catalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202611120310.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-20
AI Technical Summary
但其依旧面临着较高的电荷复合率和低太阳光谱利用率,这使得三元金属硫化锌镉固溶体在光催化重整废塑料方面的应用受限
本发明依托掺杂硫空位的Cd1-xZnxS(0<x<1)固溶体带正电、CoMo2O4尖晶石带负电的电荷差异,实现静电自组装,让掺杂硫空位的Cd1-xZnxS(0<x<1)固溶体紧密包覆在CoMo2O4尖晶石三维立方体结构表面,构筑能带高度匹配的S型异质结;复合光热催化剂中,晶格硫空位可有效抑制光生电子-空穴体相复合,CoMo2O4尖晶石的三维立方骨架还能降低界面电荷传输阻力,有效提升光电流强度与电化学活性位点数量;此外,CoMo2O4尖晶石具备优异近红外光吸收与局域表面等离子体光热转换性能,弥补传统三元金属硫化锌镉固溶体仅能利用紫外、部分可见光且无光热效应的短板,实现全光谱太阳能高效捕获,光照下可自主提升催化体系局部温度,大幅降低废塑料C-C键断裂与水解析氢的反应能垒,依靠光热协同显著加快反应动力学,复合催化剂产氢速率远高于单一光催化体系及两种单体材料;同时,复合后的材料表面亲水性更强、介孔比表面积更大,更利于水分子与塑料底物吸附接触,不仅对PLA、PET、PBS、PUR多种废塑料及真实塑料瓶原料具备良好催化普适性,还能以碱性消解后的乳酸为牺牲剂消耗光生空穴,定向高选择性生成丙酮酸等高附加值化学品,减少塑料过度氧化副产物。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts for photocatalytic reforming of waste plastics to simultaneously produce hydrogen and preparation thereof, and particularly relates to a composite photothermal catalyst, preparation method and application thereof. Background Art
[0002] Photocatalytic reforming of waste plastics is a new technology that uses waste plastics as a reaction substrate to consume holes, so as to realize photocatalytic water splitting for hydrogen production, which is regarded as a new technology to solve the environmental pollution and energy challenges caused by waste plastics. In the photocatalytic reforming process, the photocatalyst semiconductor is excited by light to generate photogenerated electrons and holes, the waste plastics as a sacrificial agent are oxidized by the photogenerated holes into high value-added chemicals, and the photogenerated electrons can reduce water to produce H2. Compared with the traditional photocatalytic water splitting, plastics are easier to oxidize due to the lower potential, thus reducing the total potential for H2 production.
[0003] Among numerous catalysts, ternary metal zinc-cadmium sulfide solid solution Cd 1-x Zn x S (0<x<1), abbreviated as CZS, has become a promising candidate material in the process of photocatalytic hydrogen production due to its excellent redox potential and chemical stability. By adjusting Cd 2+ and Zn 2+ ratio, Cd 1-x Zn x S (0<x<1) with the optimal band gap and band structure can be synthesized. However, it still faces high charge recombination rate and low utilization rate of solar spectrum, which limits the application of the ternary metal zinc-cadmium sulfide solid solution in the photocatalytic reforming of waste plastics. Contents of the Invention
[0004] In view of the problems existing in the background art, the present invention provides a photothermal catalyst, preparation method and application thereof. By introducing sulfur vacancies into CZS, and compounding the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution with CoMo2O4 spinel to construct an S-type homojunction material, the newly constructed S-type homojunction material has higher catalytic efficiency in the photocatalytic reforming of waste plastics for simultaneous hydrogen production than single CZS.
[0005] The specific contents of the invention are as follows: In a first aspect, the present invention provides a composite photothermal catalyst, and the composition of the catalyst comprises: sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution and CoMo2O4 spinel, wherein the sulfur vacancy-doped Cd 1-x Zn xS (0<x<1) solid solution is coated on the surface of the CoMo₂O₄ spinel three-dimensional cubic structure through electrostatic interaction.
[0006] Optionally, the surface water contact angle of the catalyst is smaller than that of the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution; the surface water contact angle of the catalyst is smaller than that of the CoMo₂O₄ spinel.
[0007] Optionally, the catalyst has light absorption properties of absorbing ultraviolet light, visible light and near-infrared light.
[0008] Optionally, the mass ratio of the CoMo₂O₄ spinel to the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution is 0.5-3:10.
[0009] Optionally, x=0.5.
[0010] In a second aspect, the present invention provides a preparation method of a composite photothermal catalyst, and the preparation method comprises: ultrasonically dispersing the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution and the CoMo₂O₄ spinel in deionized water, performing magnetic stirring for 4-8 h, and carrying out vacuum drying to obtain the composite photothermal catalyst described in the first aspect.
[0011] Optionally, the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution is obtained in the following manner: Dissolving zinc acetate dihydrate and cadmium acetate dihydrate in deionized water to form a mixed solution, adding an aqueous thioacetamide solution dropwise into the mixed solution, adding an appropriate amount of sodium hydroxide, transferring the obtained mixed system into a high-pressure reaction kettle, and carrying out a reaction at 120 °C-180 °C to obtain the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution.
[0012] Optionally, the CoMo₂O₄ spinel is obtained in the following manner: Dissolving cobalt nitrate hexahydrate, manganese sulfate monohydrate and ammonium sulfate in an ethanol aqueous solution to form a mixed solution, adding an ammonium bicarbonate solution dropwise to the mixed solution, allowing the obtained mixed system to react at 50 °C-80 °C for 5 h-12 h, collecting the solid material formed by the reaction, and transferring the solid material to 550 °C-750 °C for calcination treatment to obtain the CoMo₂O₄ spinel.
[0013] In a third aspect, the present invention provides an application of a composite photothermal catalyst, wherein the composite photothermal catalyst described in the first aspect above is used for photocatalytic reforming of waste plastics to simultaneously produce hydrogen.
[0014] Optionally, the composition of the waste plastic comprises polyethylene terephthalate, polyurethane and / or polybutylene succinate.
[0015] The present invention provides a composite photothermal catalyst, and the composition of the catalyst comprises: Cd doped with sulfur vacancies 1- x Zn x S (0<x<1) solid solution and CoMo₂O₄ spinel, wherein the Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution is coated on the surface of the three-dimensional cubic structure of the CoMo₂O₄ spinel through electrostatic interaction; compared with the prior art, the present invention has the following advantages: The present invention relies on the charge difference that the Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution is positively charged and the CoMo₂O₄ spinel is negatively charged to realize electrostatic self-assembly, so that the Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution is tightly coated on the surface of the three-dimensional cubic structure of the CoMo₂O₄ spinel, constructing an S-scheme heterojunction with highly matched energy bands; in the composite photothermal catalyst, lattice sulfur vacancies can effectively inhibit the bulk phase recombination of photogenerated electrons and holes, and the three-dimensional cubic framework of the CoMo₂O₄ spinel can also reduce the interfacial charge transfer resistance, effectively improving the photocurrent intensity and the number of electrochemical active sites; in addition, the CoMo₂O₄ spinel has excellent near-infrared light absorption and localized surface plasmon photothermal conversion performance, which makes up for the shortcoming of traditional ternary zinc cadmium sulfide solid solutions that can only utilize ultraviolet light and part of visible light and have no photothermal effect, realizing efficient full-spectrum solar energy capture, which can autonomously raise the local temperature of the catalytic system under illumination, greatly reduce the reaction energy barriers for the C-C bond cleavage of waste plastics and hydrogen evolution from water splitting, significantly accelerate the reaction kinetics through photothermal synergy, and the hydrogen production rate of the composite catalyst is much higher than that of a single photocatalytic system and the two monomer materials; at the same time, the composited material has stronger surface hydrophilicity and larger mesoporous specific surface area, which is more conducive to the adsorption and contact of water molecules and plastic substrates, not only has good catalytic universality for a variety of waste plastics such as PLA, PET, PBS, PUR and real plastic bottle raw materials, but also can use alkali-digested lactic acid as a sacrificial agent to consume photogenerated holes, directionally and highly selectively generate high value-added chemicals such as pyruvic acid, and reduce plastic over-oxidation by-products.
[0016] The raw materials used in the preparation of the composite photothermal catalyst provided by this invention are all common commercially available inorganic reagents. The process is mild and simple, without the doping of precious metals, and can simultaneously realize the resource-based treatment of waste plastics and the clean production of green hydrogen. It overcomes the multiple technical bottlenecks of existing photocatalytic reforming technology for waste plastics, such as low charge separation rate, narrow solar spectrum utilization rate, low efficiency of plastic conversion and hydrogen production, poor selectivity of target chemicals, and lack of photothermal self-heating synergistic system. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Scanning electron microscope image at -10; Figure 2 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X X-ray diffraction pattern at -10; Figure 3 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X -10 surface water contact angle test diagram; Figure 4 The CMO and TCZS provided in the embodiments of the present invention are shown. X Zeta potential test diagram; Figure 5 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Fourier transform infrared spectrum of -10; Figure 6 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Specific surface area and porosity test diagram at -10; Figure 7 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X -10 UV-Vis diffuse reflectance spectrum test diagram; Figure 8 The CMO and TCZS provided in the embodiments of the present invention are shown.X and MTCZS X Infrared thermal imaging test image of -10 under 300 W xenon lamp illumination; Figure 9 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Transient photocurrent response and electrochemical impedance spectroscopy at -10°C; Figure 10 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X -10 linear sweep voltammetry curve test graph; Figure 11 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Cyclic voltammetry curves, double-layer capacitance, and electrochemical active area measurements at -10°C; Figure 12 The embodiments of the present invention illustrate MTCZS under different reaction systems and catalyst conditions. X -10 Hydrogen production performance diagram of PLA waste plastics undergoing photothermal catalytic reforming; Figure 13 The embodiments of the present invention illustrate MTCZS under different initial factor conditions. X -10 Hydrogen production performance diagram of PLA waste plastics undergoing photothermal catalytic reforming; Figure 14 The MTCZS provided in the embodiment of the present invention is shown. X -10 Photothermal catalytic reforming hydrogen production performance diagram of real PLA and PET bottles; Figure 15 The MTCZS provided in the embodiment of the present invention is shown. X -10 catalyst cycle hydrogen production performance diagram; Figure 16 The MTCZS provided in the embodiment of the present invention is shown. X -10 NMR spectra of PLA waste plastic before and after photothermal catalytic reforming; Figure 17 The graph shows the cumulative amount of high value-added chemicals generated over 24 hours under different reaction systems and catalyst conditions provided in the embodiments of the present invention. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is in fact merely illustrative, and is in no way intended to limit the present invention, its application or use. Based on the embodiments of the present invention, any products identical or similar to the present invention obtained by any person under the inspiration of the present invention or by combining the features of the present invention with other prior art features shall fall within the protection scope of the present invention. Moreover, all other embodiments obtained by a person of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0020] In the examples, where no specific experimental steps or conditions are specified, the operations or conditions of conventional experimental steps described in the prior art in the relevant field can be followed. All used reagents and other instruments, of which no manufacturers are indicated, are conventional reagent products commercially available. In addition, the accompanying drawings are only schematic illustrations of the embodiments of the present invention, and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and thus repeated descriptions thereof will be omitted. Some block diagrams shown in the drawings are functional entities, which do not necessarily correspond to physically or logically independent entities.
[0021] Techniques, methods and apparatuses known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, such techniques, methods and apparatuses shall be regarded as part of the specification of the present invention.
[0022] Furthermore, the technical features involved in different embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.
[0023] In view of that in related studies, after sulfur vacancies are doped in CZS, the obtained Cd with doped sulfur vacancies 1-x Zn x S (0<x<1) solid solution (abbreviated as CZS X ) can significantly inhibit the recombination of photogenerated carriers and improve hydrogen production efficiency. Furthermore, spinel oxide CoMo₂O₄ (abbreviated as CMO) has good stability and photothermal properties under near-infrared light; and CMO and CZS X have good band structure matching, and have potential advantages for constructing S-scheme heterojunctions; therefore, in the present invention, CZS X is compounded with CMO to construct a new composite photothermal catalyst. Compared with single CZS X and CMO, the new catalytic material formed by the composite exhibits better performance in the photocatalytic reforming of waste plastics for simultaneous hydrogen production. The specific embodiments are as follows: In a first aspect, the present invention provides a composite photothermal catalyst, the composition of the catalyst comprising: Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution and CoMo₂O₄ spinel, wherein the Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution is coated on the surface of the three-dimensional cubic structure of the CoMo₂O₄ spinel through electrostatic interaction.
[0024] In specific implementation, the present invention constructs a novel photothermal catalyst system composed of sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution and CoMo₂O₄ spinel composite. Relying on electrostatic interaction, the sulfur vacancy-doped modified Cd 1-x Zn x S (0<x<1) solid solution is uniformly coated on the surface of the CoMo₂O₄ spinel with a three-dimensional cubic structure, forming a heterocomposite structure with tight interface bonding and stable structure; wherein, the Cd in the coating layer 1-x Zn x S (0<x<1) solid solution can be selectively set to have a twin structure or a conventional twin-free structure according to the preparation process and actual application requirements. The CoMo₂O₄ spinel with a three-dimensional cubic configuration serves as a functional substrate, which has the characteristics of large specific surface area, excellent structural stability and high photothermal conversion efficiency. It can not only act as a rigid skeleton to effectively inhibit the agglomeration and falling off of Cd 1-x Zn x S (0<x<1) solid solution nanoparticles, fully exposing the surface catalytic active sites, but also convert light energy into heat energy through an efficient photothermal effect, increase the local temperature of the catalytic system, reduce the activation energy of the photothermal catalytic reaction, realize the synergistic effect of heat-assisted photocatalysis, and break through the bottleneck of limited reaction efficiency of single photocatalysis. At the same time, Cd 1- x Zn xThe sulfur vacancies introduced in the S (0<x<1) solid solution are controllable anion defects, which can effectively regulate the electronic band structure of semiconductors, construct intermediate energy levels in the band gap, greatly broaden the absorption spectrum range of visible light, and improve the capture and utilization efficiency of sunlight. Moreover, the sulfur vacancies can act as efficient electron trapping sites, effectively trap photogenerated electrons, inhibit the rapid recombination of photogenerated electron-hole pairs, significantly prolong the migration lifetime of photogenerated carriers, and provide more effective active carriers for catalytic reactions. The tight heterogeneous interface formed based on electrostatic self-assembly can greatly reduce the resistance of charge cross-phase transmission, realize the rapid conduction and efficient migration of electrons and thermal energy, and construct a stable and efficient photothermal synergistic catalytic channel. Compared with the technical defects of traditional single sulfide photocatalysts, such as fast carrier recombination rate, narrow photoresponse range, easy structural deactivation, as well as insufficient catalytic activity and poor photothermal synergy of pure CoMo₂O₄ spinel, the composite photothermal catalyst provided by the present invention significantly improves the photothermal catalytic efficiency, structural stability and cycle service life of the catalyst.
[0025] In some embodiments, the surface water contact angle of the catalyst is smaller than that of the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution; The surface water contact angle of the catalyst is smaller than that of the CoMo₂O₄ spinel.
[0026] In specific implementation, the catalyst obtained by composite modification of the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution and CoMo₂O₄ spinel has a surface water contact angle significantly lower than that of the single sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution and the single CoMo₂O₄ spinel. The construction of the heterogeneous interface optimizes the surface micromorphology and surface functional group distribution of the material, greatly improves the wettability of the catalyst surface, can effectively strengthen the adsorption and enrichment capacity of waste plastic substrates in the aqueous solution system, increase the contact probability between catalytic active sites and reaction substrates, and significantly improve the catalytic reaction efficiency from the interface adsorption level.
[0027] In some embodiments, the catalyst has light absorption properties for absorbing ultraviolet light, visible light and near-infrared light.
[0028] In specific implementation, the present invention effectively broadens the spectral response range through the construction of intermediate energy levels by sulfur vacancy defects, the excellent near-infrared photothermal conversion characteristics of CoMo₂O₄ spinel and the synergistic effect of the heterojunction, realizes the efficient utilization of full-spectrum solar energy, takes into account the dual effects of photocatalysis and photothermal catalysis, and greatly improves the solar energy utilization rate and the driving force of the catalytic reaction.
[0029] In some embodiments, the mass ratio of the CoMo₂O₄ spinel to the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution is 0.5-3:10.
[0030] In specific implementation, the mass ratio of the two active components, the CoMo₂O₄ spinel and the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution, is controlled at 0.5-3:10, preferably at a mass ratio of 1:10, which effectively avoids problems such as particle agglomeration, increased interfacial resistance, and shielding of active sites caused by excess of a single component, maximizes the photothermal synergistic effect between the photocatalytic activity of the sulfur vacancy-containing Cd 1-x Zn x S (0<x<1) solid solution and the CoMo₂O₄ spinel, and realizes the matching of catalytic performances.
[0031] In some embodiments, x=0.5.
[0032] In specific implementation, when the Cd 1-x Zn x S (0<x<1) solid solution has a twin crystal structure, the twin interface can construct a natural built-in electric field, drive the directional migration of photogenerated carriers, further strengthen the charge separation efficiency, and maximize the photothermal catalytic activity of the catalyst; therefore, the present invention preferably adopts the Cd 0.5 Zn 0.5 S solid solution with x=0.5 (abbreviated as TCZS x ) in the proportion, the Cd 0.5 Zn 0.5 S solid solution containing nano-twin sulfur vacancies is tightly coated on the surface of three-dimensional cubic CMO, constructing an S-type homojunction with highly matched energy bands. The alternating structure of sphalerite and wurtzite inside the twin crystal combined with lattice sulfur vacancies can doubly inhibit the bulk phase recombination of photogenerated electrons and holes, can maximally retain the electron trapping and energy band regulation effects of sulfur vacancies, and simultaneously realize perfect interface matching with the CoMo₂O₄ spinel, further reducing the charge transmission resistance and ensuring the efficient catalytic performance of the composite catalyst.
[0033] In a second aspect, the present invention provides a preparation method of a composite photothermal catalyst, the preparation method comprising: ultrasonically dispersing the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution and the CoMo₂O₄ spinel in deionized water, magnetically stirring for 4-8 h, and performing vacuum drying to obtain the composite photothermal catalyst according to the above first aspect.
[0034] In specific implementation, the present invention completes the preparation of the catalyst through a physical composite method combining ultrasonic dispersion and magnetic stirring, paired with vacuum drying treatment, without the need for complex high-temperature and high-pressure processes. The operation is simple, the process has good reproducibility, the preparation cost is low, it meets the demands of industrial large-scale production, and the process can fully preserve the intrinsic structures and active sites of the two materials, ensuring the photothermal synergistic performance of the composite catalyst.
[0035] In some embodiments, the Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution can be a commercially available industrial finished product, and can also be obtained by the following method: Dissolve zinc acetate dihydrate and cadmium acetate dihydrate in deionized water to form a mixed solution, drop an aqueous thioacetamide solution into the mixed solution, add an appropriate amount of sodium hydroxide, transfer the obtained mixed system to a high-pressure reactor, and react at 120 °C-180 °C to obtain the Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution.
[0036] In some embodiments, the CoMo₂O₄ spinel can be a commercially available industrial finished product, and can also be obtained by the following method: Dissolve cobalt nitrate hexahydrate, manganese sulfate monohydrate and ammonium sulfate in an aqueous ethanol solution to form a mixed solution, drop an ammonium bicarbonate solution into the mixed solution, react the obtained mixed system at 50 °C-80 °C for 5 h-12 h, collect the solid material formed by the reaction, and transfer it to calcination treatment at 550 °C-750 °C to obtain the CoMo₂O₄ spinel.
[0037] In a third aspect, the present invention provides an application of a composite photothermal catalyst, wherein the composite photothermal catalyst described in the first aspect above is used for photocatalytic reforming of waste plastics to produce hydrogen synchronously.
[0038] Optionally, the composition of the waste plastics includes polyethylene terephthalate, polyurethane and / or polybutylene succinate.
[0039] To enable those skilled in the art to understand the present invention more clearly, the composite photothermal catalyst, the preparation method and the application thereof according to the present invention will now be described in detail through the following examples.
[0040] The following reagents used in the examples, including cadmium acetate dihydrate (Cd(Ac)₂·2H₂O), zinc acetate dihydrate (Zn(Ac)₂·2H₂O), thioacetamide (C₂H₅NS), sodium hydroxide (NaOH), cobalt nitrate hexahydrate (Co(NO₃)₂·6H₂O), manganese sulfate monohydrate (MnSO₄·H₂O), ammonium sulfate ((NH₄)₂SO₄), ammonium bicarbonate (NH₄HCO₃), and ethanol, were all purchased from Aladdin (Shanghai, China). All reagents were ready to use without further purification. All experiments used ultrapure water (>18.2 MΩ). cm Millipore).
[0041] Example 1 Step 1: Dissolve 2.20 g of zinc acetate dihydrate and 2.66 g of cadmium acetate dihydrate in 20 mL of ultrapure water, denoted as solution A. Dissolve 1.88 g of thioacetamide in 20 mL of ultrapure water, denoted as solution B. After vigorous stirring for 30 min, add solution B dropwise to solution A, continuing stirring for another 30 min. Then add 1.60 g of sodium hydroxide to the mixed solution and stir for 30 min. Finally, transfer the solution to a Teflon-lined stainless steel autoclave and perform hydrothermal synthesis at 180 °C for 24 h. After cooling to room temperature, wash the sample three times alternately with ultrapure water and ethanol, and vacuum dry at 80 °C for 10 h to obtain TCZS. X Material.
[0042] Step 2: Dissolve 0.93 g of cobalt nitrate hexahydrate, 1.13 g of manganese sulfate monohydrate, and 13.21 g of ammonium sulfate in a mixture of 700 mL of ultrapure water and 70 mL of ethanol, stirring continuously for 15 min. This solution is designated as solution A. Dissolve 7.91 g of ammonium bicarbonate in 700 mL of ultrapure water, stirring continuously for 15 min. This solution is designated as solution B. Solution B is then slowly added to solution A, stirring continuously for 15 min. The mixture is then placed in a water bath and stirred continuously at 50 °C for 9 h. After stirring, the mixture is filtered, washed, and vacuum dried at 60 °C for 12 h to obtain Co. 0.33 Mn 0.67 CO3 is a pink solid. Finally, Co... 0.33 Mn 0.67 Pink CO3 solid was poured into a corundum ark and placed in a tube furnace. Under an air atmosphere, the temperature was increased to 600 °C at 2 °C / min and held for 5 h. After cooling to room temperature, the powder was collected to obtain green CMO nanoparticles.
[0043] Step 3: Add 0.20 g TCZS X20 mg CMO was dispersed in 20 mL of ultrapure water and sonicated and vibrated for 2 h. Then, the mixture was magnetically stirred for 6 h. Finally, the solution was placed in a vacuum drying oven and vacuum dried for 24 h to obtain the composite photothermal catalyst (MTCZS). X -10).
[0044] Figure 1 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Scanning electron microscope image at -10°C Figure 1 a is a scanning electron microscope image of CMO. Figure 1 b is TCZS X Scanning electron microscope, Figure 1 c is MTCZS X -10 scanning electron microscope, such as Figure 1 a- Figure 1 As shown in c, the CMO synthesized by high-temperature calcination exhibits a regular three-dimensional cubic structure, TCZS X These are zero-dimensional nanoparticles with an average particle size of 60 nm. After electrostatic ultrasonic self-assembly, TCZS... X Zero-dimensional nanoparticles are coated on the surface of a CMO three-dimensional cube to form a tightly bonded composite material.
[0045] Figure 2 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X X-ray diffraction pattern at -10, as shown Figure 2 As shown, TCZS X The diffraction peaks exhibit characteristics of both zincblende and wurtzite crystal structures, and are consistent with the diffraction peaks of cubic ZnS (PDF#05-0566) and hexagonal CdS (PDF#41-1049), but these peaks are not entirely identical to those of ZnS and CdS. Compared to ZnS, TCZS... X The peak shifts to a lower angle, and due to Zn 2+ The radius (0.074 nm) is smaller than that of Cd. 2+ (0.097 nm), its peak value is slightly higher than that of CdS. When Zn 2+ When CZS enters the CdS lattice, the lattice constant decreases, causing the diffraction peaks of the prepared sample to shift to higher angles. The results indicate that the synthesized CZS is not a simple mixture of CdS and ZnS or a CdS / ZnS heterostructure, but rather a twinned CZS. X The characteristic peaks of CMO are located at 18.16°, 29.35°, 30.90°, 33.35°, 36.07°, 44.26°, 58.36°, 60.89°, and 64.38°, which are similar to those of CMO. Figure 2It is consistent with the standard card (PDF#77-0471) in the MTCZS. X -10 clearly shows the presence of CMO and TCZS. X The characteristic peaks indicate the successful preparation of the composite material.
[0046] Figure 3 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X -10 surface water contact angle, such as Figure 3 As shown in the figure, generally, the smaller the surface water contact angle, the better the surface hydrophilicity of the material. The figure shows TCZS... X The surface water contact angle of the composite material is 29.4°, while that of CMO is 42.7°. After the two are combined, the surface water contact angle is reduced to 26.3°. The enhanced hydrophilicity of the composite material facilitates the adsorption and dissociation of water molecules, thereby promoting the efficient conduct of the hydrogen evolution reaction.
[0047] Figure 4 The CMO and TCZS provided in the embodiments of the present invention are shown. X Zeta potential diagram, such as Figure 4 As shown, TCZS X With a positive charge of +11.27 mV and a negative charge of -6.03 mV, CMO indicates that electrostatic attraction occurs between the two monomers during electrostatic ultrasonic self-assembly, forming a tightly bound aggregate structure.
[0048] Figure 5 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X The Fourier transform infrared spectrum of -10 is shown below. Figure 5 As shown, 525 cm in CMO -1 and 630 cm -1 The absorption peaks at 1637 cm⁻¹ are attributed to the stretching vibrations of the Mn-O and Co-O bonds, respectively. -1 and 3200-3600 cm -1 The absorption peak at that point is attributed to the bending vibration of HOH; for TCZS X , at 1021-1413 cm -1 Stretching vibrations of Cd-S and Zn-S can be observed within the range, at 1552 cm⁻¹. -1 and 3200-3600 cm -1 The absorption peak at that location originates from the bending vibration of HOH, indicating that water molecules are adsorbed on the sample surface. CMO and TCZS X All characteristic absorption peaks were observed in the composite material, confirming the successful preparation of the composite material.
[0049] Figure 6 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X The specific surface area and porosity test results for -10 are shown in the following figures. Figure 6 As shown, based on existing nitrogen adsorption-desorption isotherm types, the nitrogen adsorption-desorption isotherm type of CMO is type IV, TCZS X and MTCZS X -10 are all type III, indicating CMO and TCZS X and MTCZS X -10 are all mesoporous structures. Furthermore, compared to TCZS... X MTCZS X -10 has a larger specific surface area, indicating that the composite material has more active sites available for the hydrogen evolution reaction.
[0050] Figure 7 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X The UV-Vis diffuse reflectance spectrum at -10 is shown in the figure. Figure 7 As shown, TCZS X The light absorption boundary is 510 nm, indicating that it can absorb ultraviolet light and part of the visible light; CMO exhibits a broad spectral response from the ultraviolet to the near-infrared region. MTCZS X The -10 light absorption boundary redshift exhibits excellent light absorption performance in the ultraviolet-visible-near-infrared range, and the light capture efficiency is also significantly improved, which fully combines the advantages of CMO and TCZS. X Its light absorption characteristics.
[0051] Figure 8 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Infrared thermal imaging test image of -10 under 300 W xenon lamp illumination, as shown Figure 8 As shown, CMO exhibits a significant photothermal effect. With an initial temperature of 55.1 °C, its surface temperature significantly increased to 82.7 °C after 600 s of illumination, indicating its efficient conversion of incident light energy into heat energy. Due to the lack of a photothermal effect, TCZS… X After 600 seconds of continuous irradiation, the surface temperature change was small, indicating that it was difficult to convert solar energy into heat energy. However, when the two were combined, the MTCZS... X The surface temperature at -10°C rose rapidly to 83.2 °C, demonstrating that photothermal synergistic catalysis is beneficial for overcoming the reaction energy barrier and improving the efficiency of the catalytic process.
[0052] Figure 9 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Transient photocurrent response and electrochemical impedance spectroscopy at -10°C are shown in the figure. Figure 9 As shown, with CMO and TCZS X In comparison, MTCZS X -10 exhibits a stronger photocurrent response, indicating that the composite material can promote the generation of photogenerated carriers and suppress the recombination of photogenerated carriers. Figure 9 a). In addition, from Figure 9 You can see MTCZS in b. X -10 has a smaller impedance radius. Generally, a smaller impedance radius indicates lower interfacial charge transfer impedance, which is beneficial for rapid charge transport.
[0053] Figure 10 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X The linear sweep voltammetry curve test plot of -10 is shown below. Figure 10 As shown, with CMO and TCZS X In comparison, MTCZS X -10 has a lower onset potential and a higher current density, indicating that it has stronger hydrogen evolution reaction activity.
[0054] Figure 11 The CMO and TCZS provided in the embodiments of the present invention are shown. X and MTCZS X Cyclic voltammetry, double-layer capacitance, and electrochemical active area measurements at -10°C are shown in the figure. Figure 11 As shown, the double-layer capacitance of the catalyst was calculated by testing cyclic voltammetry curves at different voltages, and then the electrochemically active surface area was analyzed. (10-200 mV) s -1 Within the scan rate range, for CMO, TCZS X and MTCZS X Fitting the cyclic voltammetry curves at -10 ( Figure 11 a, Figure 11 c). The results showed that, compared with monomeric CMO and TCZS X MTCZS X -10 exhibits higher double-layer capacitance and electrochemical active area ( Figure 11 d and Figure 11 e) indicates that the composite material has more electrochemical active sites, thus exhibiting superior hydrogen evolution efficiency.
[0055] Performance testing: MTCZS prepared using Example 1X The performance of a -10 photothermal catalyst in hydrogen production and the reforming of PLA waste plastics into high-value-added chemicals was verified. The experiment of simultaneous hydrogen production and high-value-added chemical generation from PLA waste plastics via photothermal catalytic reforming was conducted in a 50 mL double-walled sealed quartz beaker. The specific experimental steps are as follows: Before the experiment, 2.5 g of PLA waste plastic was dissolved in 100 mL of 10 M KOH solution and stirred continuously at 60 °C for 24 h to alkaline digest it into LA for later use. Then, 1.5 mg of catalyst was ultrasonically dispersed in 20 mL of PLA alkaline digestion solution, and the reactor was purged with N2 for 20 min to create an inert atmosphere. A 300 W xenon lamp (λ>420 nm, 150 mW / cm²) was then used. 2 Full-spectrum irradiation was performed without circulating water cooling. At preset time points, 2.0 mL of headspace gas sample was injected into a gas chromatograph (Agilent 7890A, N2 carrier gas, 5 Å molecular sieve) equipped with a thermal conductivity detector. The H2 concentration in the reaction gas was measured and the hydrogen production rate (mmol·g) was calculated. -1 ·h -1 ).
[0056] Hydrogen production rate calculation:
[0057] (1) Total H2 Total H2 = H2 dissolved in the reaction solution + H2 from headspace (2) Headspace H2
[0058]
[0059] Where 24.5 represents the ideal gas at 25 °C, 1.01 × 10⁻⁶ 5 The gas molar volume (L / mol) at Pa; 93 is the headspace volume (mL); 8878.84 is the slope of the standard curve.
[0060] (3) H2 dissolved in the reaction solution
[0061] Where 0.01907 is the Henry's constant; 20 is the volume of the reaction liquid (mL).
[0062] Determination of high value-added chemicals: Qualitative and quantitative analysis of high-value-added chemicals after photocatalytic reforming was performed using a nuclear magnetic resonance (NMR) spectrometer (Brook Avance NEO 600, 600 MHz). For testing, 1 mL of the reaction solution was diluted four times with ultrapure water to avoid instrument tuning failure due to high salt concentrations. Subsequently, 400 μL of the diluent, 400 μL of heavy water, and 4 mg of maleic acid were added to the NMR tube, and analysis was performed using the water suppression method. Quantitative analysis of the high-value-added chemicals was then performed according to the following formula.
[0063]
[0064] Where n, S, m, and N represent the amount of substance (mol), the area of the integral peak, the mass (g), and the number of protons, respectively.
[0065] Cyclic experiment: After the first reaction was completed, the solution containing the photocatalyst was centrifuged, and the lower layer of material was vacuum dried overnight at 60 °C. Then, it was placed back into the reactor for the second experiment. Except for the material, the other reaction conditions were kept the same as in the first experiment. After the second reaction was completed, the above steps were repeated for the third, fourth, and fifth experiments.
[0066] Photothermal effect test: MTCZS X The -10 powder sample was evenly spread and placed 15 cm away from the light source. A 300 W xenon lamp (λ>420 nm, 150 mW / cm²) was used. 2 The catalyst is irradiated with the full spectrum without circulating water cooling. At preset time points, the surface temperature of the catalyst is recorded using an infrared thermal imager (UNI-T, Uti260E).
[0067] Figure 12 MTCZS was shown under different reaction systems and catalyst conditions. X -10 Photothermal catalytic reforming of PLA waste plastics hydrogen production performance, such as Figure 12 a- Figure 12 As shown in b, for pure CMO, the amount of H2 produced is almost negligible due to insufficient reducing power. TCZS X The hydrogen production rate was 13.42 mmol·g. -1 ·h -1 It exhibits high hydrogen production activity. After the two are combined, MTCZS X The hydrogen production rate at -10 was significantly increased to 40.13 mmol·g -1 ·h -1 This is because the formation of the heterojunction suppresses the recombination of photogenerated carriers, thus allowing more photogenerated electrons to be used for the reduction of H. + H2 is produced. For example... Figure 12 c- Figure 12 As shown in Figure d, no H2 generation was detected in the systems without catalyst, without PLA waste plastic, or without alkaline digestion of PLA waste plastic; similarly, no H2 was detected in the thermocatalytic system alone, indicating that thermal energy mainly plays an auxiliary role in photocatalysis. During the reaction, the alkaline pretreated PLA waste plastic acts as a sacrificial agent, increasing hydrogen production activity by consuming holes, while the absence of PLA waste plastic leads to rapid recombination of photogenerated carriers, thus greatly inhibiting hydrogen evolution activity. It is noteworthy that compared to the photocatalytic system alone (18.51 mmol·g), -1 ·h -1 ), MTCZS X The hydrogen production rate of the -10 photothermal synergistic system increased significantly to 40.13 mmol·g⁻¹. -1 ·h -1 This indicates that the catalytic process is triggered by photogenerated carriers and promoted by thermal energy.
[0068] Figure 13 The MTCZS values under different CMO doping ratios, different potassium hydroxide concentrations, different PLA concentrations, and different types of waste plastics are shown. X -10 Photothermal catalytic reforming of PLA waste plastics hydrogen production performance, among which... Figure 13 The hydrogen evolution activity of the composite material under different CMO doping ratios was investigated. The hydrogen evolution rate gradually increased with increasing CMO ratio, with MTCZS showing the highest rate. X -10 performed best. Excessive CMO addition led to a decrease in hydrogen production because excess CMO interferes with charge excitation and migration processes and masks active sites, which is detrimental to H2 production. + Restored to H2; Figure 13 b. The hydrogen evolution activity of the composite material at different PLA concentrations was investigated. As the PLA concentration increased from 5 to 45 mg / mL, the MTCZS... X The photothermal hydrogen production rate of -10 significantly increased from 9.77 to 40.13 mmol·g -1 ·h -1 This is because higher concentrations of PLA waste plastic release more LA monomers during alkaline digestion, which consumes more holes and thus greatly increases hydrogen production activity. However, considering the substrate conversion rate and conversion efficiency, 25 mg / mL was ultimately chosen for subsequent studies. Figure 13 c shows MTCZS X -10 Hydrogen evolution activity at different potassium hydroxide concentrations. As the potassium hydroxide concentration increases from 1 to 10 M, the hydrogen production rate rapidly increases from 9.39 to 40.13 mmol·g⁻¹. -1 ·h -1The increase in alkali concentration not only improves the solubility of PLA waste plastics, enabling them to decompose and produce more LA monomers, but also enhances the dissociation of water, thereby increasing hydrogen production activity; Figure 13 d shows MTCZS X -10 Photothermal catalytic reforming of polyethylene terephthalate (PET), polyurethane (PUR), and polybutylene succinate (PBS) showed hydrogen evolution activity. The figure shows that the hydrogen production rates of PET, PUR, and PBS were 15.39, 10.22, and 29.16 mmol·g, respectively. -1 ·h -1 This indicates that MTCZS X -10 catalyst has good universality for different types of waste plastics.
[0069] Figure 14 MTCZS is shown X -10 Photothermal catalytic reforming hydrogen production performance in real PLA and PET bottles, such as Figure 14 As shown, the hydrogen production rates of the actual PET and PLA bottles were 16.15 and 21.80 mmol·g, respectively. -1 ·h -1 .
[0070] Figure 15 MTCZS is shown X -10 The hydrogen production performance of PLA waste plastics after 5 cycles of continuous photothermal catalytic reforming, such as Figure 15 As shown, compared to the initial cycle, the hydrogen evolution activity remained above 94.34% in the 5th cycle, indicating that the efficiency of MTCZS... X -10 exhibits good stability.
[0071] Figure 16 MTCZS is shown X -10. The 1H NMR spectra of PLA waste plastic before and after photothermal catalytic reforming. As can be seen from the figure, after 24 h of photothermal catalytic reforming, the lactic acid peak intensity significantly decreased, and it was efficiently converted into pyruvate and a small amount of acetate, exhibiting high selectivity for pyruvate.
[0072] The photothermal catalytic reforming performance of the catalyst was further evaluated by comparing the cumulative 24-hour formation of high-value-added chemicals under different reaction systems and catalyst conditions. For example... Figure 17As shown in figure a, no pyruvate and acetic acid were generated in the systems without catalyst, without PLA waste plastic, without alkaline digestion of PLA waste plastic, or in the thermocatalytic system alone. However, in the photocatalytic system alone, the cumulative amounts of pyruvate and acetic acid were only 421.63 and 19.39 μmol, respectively. After the introduction of heat, the cumulative amounts of the corresponding products rapidly increased to 1117.15 and 144.62 μmol. It is worth noting that pure TCZS… X Composition of high-value-added chemicals obtained from catalytic substrate oxidation and MTCZS X -10 is similar, but pure CMO, due to its deeper valence band, only produces a small amount of high-value-added chemicals ( Figure 17 b).
[0073] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0074] For the sake of simplicity, the method embodiments are described as a series of actions. However, those skilled in the art should understand that the present invention is not limited to the described order of actions, as some steps can be performed in other orders or simultaneously according to the present invention. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions and components involved are not necessarily essential to the present invention.
[0075] The present invention provides a detailed description of a composite photothermal catalyst, its preparation method, and its application. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only intended to help understand the method and core ideas of the present invention. At the same time, those skilled in the art will recognize that, based on the ideas of the present invention, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A composite photothermal catalyst, characterized in that, The composition of the catalyst comprises: Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution and CoMo₂O₄ spinel, wherein the Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution is coated on the surface of the three-dimensional cubic structure of the CoMo₂O₄ spinel through electrostatic interaction.
2. The composite photothermal catalyst according to claim 1, characterized in that, The surface water contact angle of the catalyst is smaller than the surface water contact angle of the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution; The surface water contact angle of the catalyst is smaller than that of the CoMo2O4 spinel.
3. The composite photothermal catalyst according to claim 1, characterized in that, The catalyst has light absorption properties that absorb ultraviolet light, visible light, and near-infrared light.
4. The composite photothermal catalyst according to claim 1, characterized in that, The mass ratio of the CoMo₂O₄ spinel to the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution is 0.5-3:
10.
5. The composite photothermal catalyst according to claim 1, characterized in that, x=0.5。 6. A method for preparing a composite photothermal catalyst, characterized in that, The preparation method comprises: subjecting Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution and CoMo₂O₄ spinel to ultrasonic dispersion in deionized water, magnetically stirring for 4-8 h, and performing vacuum drying, to obtain the composite photothermal catalyst according to any one of claims 1 to 5.
7. The method for preparing the composite photothermal catalyst according to claim 6, characterized in that, The Cd doped with sulfur vacancies 1-x Zn x S (0<x<1) solid solution is obtained in the following manner: Zinc acetate dihydrate and cadmium acetate dihydrate are dissolved in deionized water to form a mixed solution, an aqueous thioacetamide solution is added dropwise to the mixed solution, an appropriate amount of sodium hydroxide is added, the resulting mixed system is transferred to a high-pressure reactor, and the reaction is carried out at 120°C to 180°C to obtain the sulfur vacancy-doped Cd 1-x Zn x S (0<x<1) solid solution.
8. The method for preparing the composite photothermal catalyst according to claim 6, characterized in that, The CoMo2O4 spinel is obtained through the following method: Cobalt nitrate hexahydrate, manganese sulfate monohydrate, and ammonium sulfate were dissolved in an aqueous ethanol solution to form a mixed solution. Ammonium bicarbonate solution was added dropwise to the mixed solution. The resulting mixture was reacted at 50 ℃-80 ℃ for 5 h-12 h. The solid material formed by the reaction was collected and transferred to calcination at 550 ℃-750 ℃ to obtain the CoMo2O4 spinel.
9. An application of a composite photothermal catalyst, characterized in that, The composite photothermal catalyst described in any one of claims 1-5 is used for photocatalytic reforming of waste plastics to produce hydrogen simultaneously.
10. The application of the composite photothermal catalyst according to claim 9, characterized in that, The waste plastics consist of polyethylene phthalate, polyurethane, and / or polybutylene succinate.